Saint Joseph of Lisbon: a counterrreformation neighbourhood - Barros, Miguel Monteiro de (2019)
This article examines the development of the São José neighbourhood in Lisbon and how that development was closely connected  with the Catholic Reformation. In 1567, in the aftermath of the Council of Trent, a hermitage dedicated to Saint Joseph, situated close by one of the main access roads into Lisbon, was transformed into the headquarters of a new parish. The choice of Saint Joseph as  parish patron was not a mere coincidence. It made part of a deliberate strategy of dissemination of the Counter Reformation  ideology, making use of the basic administrative cell of the Catholic Church, the parish. The compulsory requirement for parochial registers and for the participation of the faithful in the religious acts contributed decisively to the formation of communitary bonds  among the neighbours of Bairro de São José.